Therapeutic effects of curcumin on the functional disturbances and oxidative stress induced by renal ischemia/reperfusion in rats - Houshang Najafi; Saeed Changizi Ashtiyani; Sayed Abolhasan Sayedzadeh; Zeynab Mohamadi yarijani; Sajad Fakhri (Mashhad University of Medical Sciences, 2015)
Objectives: Curcumin has anti-inflammatory and antioxidative properties. The objective of this study was to investigate the therapeutic effects of curcumin on functional disturbances, oxidative stress, and leukocyte infiltration induced by renal ischemia/reperfusion (I/R). Materials and Methods: Animals were randomly divided into 9 groups. The groups with 24-h reperfusion consisted of sham-24h, I/R-24h, and three I/R groups treated with curcumin at 10, 20, or 30 mg kg-1, i.p. after the ischemic period. The 72-h reperfusion groups also included Sham-72h, I/R-72h, I/R treated with curcumin at single dose of 20 mg kg-1, i.p., and I/R group which received three doses of curcumin at 20 mg kg-1, i.p., consecutively. Renal functional injury was assessed by measuring serum creatinine and urea-nitrogen concentrations. Oxidative stress was evaluated by assessment tissue malondialdehyde (MDA) and the ferric reducing/antioxidant power (FRAP) levels. Moreover, renal tissue leukocyte infiltration was measured by histopathology examination. Results: Ischemia/reperfusion resulted in a significant increase in serum concentration of creatinine, urea-nitrogen, tissue MDA level, and leukocytes infiltration as well as reduced FRAP level. Treatment with curcumin in 24-h reperfusion groups could only lead to a significant change in the levels of MDA and FRAP. However, in 72-h reperfusion groups, curcumin was able to correct all functional disturbances, oxidative stress, and leukocytes infiltration with more effectiveness in groups that received three doses of curcumin. Conclusion: The administration of curcumin during 72-h reperfusion following 30 minutes of ischemia can decrease renal oxidative stress and leukocytes infiltration as well as improve kidney function. However, during first 24-h reperfusion, curcumin only decreased oxidative stress.